PENGELOLAAN KEMASAN PANGAN LOKAL SLONDOK UNTUK MENINGKATKAN POTENSI PENJUALAN SAAT PANDEMI COVID-19 DI DESA KENALAN KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Nurul Anindyawati; Putri Laeshita (Fakultas Pertanian_Universitas Tidar, 2023)
Slondok is one of the typical traditional foods originating from the Magelang Regency. Slondok is a food made from cassava and is one of the foods that are in great demand by the local community or those from outside the region. However, currently, the production of slondok is still carried out traditionally and is one of the micro-home industry businesses. One of the village centers for slondok production is in Balesari Village, Windusari District, Magelang Regency. The people of this village produce slondok in simple plastic packaging. This causes slondok to be vulnerable to damage and the absence of good packaging labels so that the characteristics or identity of slondok become less well known. Packaging is very important in protecting the product, increasing storage time, and functions in attracting consumers. Therefore, training on the packaging was carried out in order to create safe, healthy and attractive packaging so that it is hoped that the sales of slondok will increase and could increase income. The method used is to carry out presentation and demonstration methods on how to choose good packaging, then monitor the program's sustainability and evaluate it. The result of the service program is that the packaging used to wrap slondok is still very simple, in the form of plastic rope. The community looked enthusiastic and discussed actively during the program. This is because good packaging products in addition to attracting consumer interest will also increase the selling price of slondok products on the market.